THE EFFECTIVENESS OF THE 'KEMBANG RANDU' WEBSITE IN SUPPORTING PUBLIC SERVICE TRANSFORMATION IN RANDUPITU VILLAGE, PASURUAN REGENCY - Nuzulla, Mei Firdaus; Agustina, Isna Fitria (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The research aims to analyze how digitalization through the "Kembang Randu" platform improves efficiency, transparency, and the quality of services at the village level. Method: A qualitative approach was employed with data collection techniques including observation, interviews, documentation, and literature review. The analysis was conducted using five effectiveness indicators: program success, target success, program satisfaction, input-output balance, and achievement of overall objectives. Results: The findings indicate that the "Kembang Randu" website has been relatively effective in providing accessible administrative services, enhancing community participation, and accelerating service processes. Nevertheless, challenges remain, particularly in terms of limited internet infrastructure, low digital literacy among residents, and the need for technical feature improvements. Novelty: This study contributes by applying a multidimensional effectiveness framework to assess digital service innovation at the village level, offering insights into the importance of infrastructure reinforcement, human resource capacity-building, and youth engagement as digital volunteers to ensure sustainable public service transformation.